Pelatihan terstruktur: usaha peningkatan kompetensi guru dalam penulisan artikel jurnal ilmiah - Afrianto Daud; Ando Fahda Aulia; Nita Rimayanti; Mirza Hardian (Unri Conference Series: Community Engagement, 2020)
The ability to publish articles in scientific journals is among the parts of a teacher's professional competence. The problem is that many teachers have not mastered the skills to write scientific papers. As a result, many teachers find it difficult to advance in rank, especially for promotion after IV / a. This paper describes a community service activity sponsored by Universitas Riau lecturers which aims to help teachers improve their scientific writing skills. Community service activities were carried out at a school in Pekanbaru, Riau. This paper further explains the concept of the workshop, the content of workshop materials, and the workshop's effectiveness. This workshop lasted for two months with three face-to-face training. The rest was done online via the Google Classroom platform. The material content covers the basic principles of scientific writing, the steps for writing scientific journals, how to cite and make references, including how to automatically cite using reference manager applications such as Mendeley, and how to submit articles through the online journal OJS system. Data from the survey conducted at the end of the community service activity showed that, in general, this activity was running well and effectively. The majority of participants (72.7%) stated that their motivation to write increased after attending the training. Their knowledge of writing scientific articles have improved after training. Their ability in writing scientific journals is also relatively better than before following this structured workshop.